2,4,6-Trimethyl-N-[3-(trifluoromethyl)phenyl]benzenesulfonamide increases calcium influx in lipopolisaccharide-pre-treated arteries - Grześk, Elżbieta (Exp Ther Med, 2017)
It has been demonstrated that 2,4,6-trimethyl-N-[3-(trifluoromethyl)phenyl]benzenesulfonamide (m-3M3FBS) activates phospholipase C (PLC) and stimulates apoptosis in smooth muscle cells, which may increase vascular reactivity. The primary aim of the present study was to evaluate the physiological effects of the direct stimulation of PLC by m-3M3FBS on vascular smooth muscle reactivity in arteries pre-treated with lipopolysaccharides (LPS) as a model of septic shock. Experiments were performed on isolated and perfused tail arteries of Wistar rats. The contraction force in the model was measured by assessing increases in perfusion pressure at a constant flow. Parameters describing the concentration-response curves (CRCs) obtained for phenylephrine and arginine-vasopressin in the presence of LPS confirmed a decrease in vessels reactivity. In comparison with the controls, m-3M3FBS treatment caused a significant increase in LPS-untreated as well as pre-treated arteries. Furthermore, in the presence of m-3M3FBS, calcium influx from intra- as well as extracellular calcium stores was significantly higher for LPS-untreated and pre-treated arteries. The results of the present study suggested that m-3M3FBS significantly increased the reactivity of vascular smooth muscle cells pre-treated with LPS by increasing the calcium influx from intra- and extracellular calcium stores. Further studies investigating this mechanism are required to evaluate whether this pathway may be a potential therapeutic strategy to treat sepsis.